Use of surface response methodology to optimize the manufacture of a nanostructured material composed of nylon nanowires with graphene - Coba D., Sebastián (2017)
In the present work, two experimental designs were carried out to find the optimal conditions to manufacture nylon nanowires and to synthesize graphene. The results obtained were: 0.68 M (NH4)2SO4 and 11.45 V; and 27 kV, 2.3 mL / h and 11.40 cm as the distance from the needle to the collector, respectively. This way, nylon nanowires and graphene were produced, both of nanometric size. Using these materials, a nanowire/graphene composite was prepared using optimum manufacturing conditions. The materials obtained (nylon nanowires, graphene and composite) were characterized morphologically (SEM) and chemically (FTIR, UV), verifying their nanometric scale, functional groups and their UV blocking properties. This work opens new perspectives for the use of recycled nylon to obtain electrospinned nano‐fibers that can be functionalized, in this case with graphene, and exhibit interesting properties for industrial applications, such as the fabrication of textile, among others.